Corrigendum on: Efficient Posterior Sampling for Bayesian Poisson Regression (Journal of computational and graphical statistics, 2025)
This corrigendum addresses errors identified in the published version of "Efficient posterior sampling for Bayesian Poisson regression," by D'Angelo and Canale ( 2023 , Volume 32, pages 917-926). The corrections pertain mainly to the discussion around Equations (8) and (9) related to a method to choose the tuning parameters r i .